Comparative benefit and cost‐effectiveness of mailed‐out faecal immunochemical tests vs collection at the general practitioner. Issue 10 (8th March 2021) - Peterse, Elisabeth F. P.; Osoro, Caroline B.; Bardou, Marc; Lansdorp‐Vogelaar, Iris
Summary: Background: Participation in the colorectal cancer screening programme in France has been well below the 45% considered acceptable by European guidelines, potentially attributable to the need to collect the faecal immunochemical test (FIT) at the general practitioner. Aim: To estimate the potential benefits and costs of including the FIT in the invitation letter. Methods: A well‐established microsimulation model was used to simulate the French population 35 years and older in 2018. We estimated quality‐adjusted life‐years (QALY) gained, costs and cost‐effectiveness of the current screening programme, and compared it to a variation of the programme where the FIT was mailed to participants and adherence was assumed to increase to 45%. We also estimated the threshold increase in participation needed to make this intervention cost‐effective. Results: Under the current programme, 53.8 colorectal cancer (CRC) cases and 25.2 CRC deaths per 1000 individuals are expected to occur over a lifetime. If sending out the FIT increases screening participation to 45%, this intervention would result in 6% fewer CRC deaths and 3% fewer CRC cases, resulting in an estimated cost‐effectiveness ratio of €2149 per QALY gained. Sending out the FIT would only need to increase participation by 0.7% point for this intervention to be considered cost‐effective. Conclusion: Including the FIT in the invitation letter is likely a very cost‐effective intervention to increase participation in CRC screening. These results for France are also informative for many other countries around the world where FIT needs to be collected at pharmacies or general practitioners.